2019
DOI: 10.1016/j.cis.2019.101990
|View full text |Cite
|
Sign up to set email alerts
|

Microgels at fluid-fluid interfaces for food and drinks

Abstract: Various aspects of microgel adsorption at fluid-fluid interfaces of relevance to emulsion and foam stabilization have been reviewed. The emphasis is on the wider non-food literature, with a view to highlighting how this understanding can be applied to food-based systems. The various different types of microgel, their methods of formation and their fundamental behavioral traits at interfaces are covered. The latter includes the aspects of microgel deformation and packing at interfaces, their deformability, size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 129 publications
(179 reference statements)
0
39
0
Order By: Relevance
“…All in all, our study opens the way for the investigation of microgels at the interface as a simple realization of 2D elastic particles. We expect that the evidence reported here will have important consequences on the study of twodimensional elastic objects at the fundamental level [90,91] and for the clever design of composite materials [92][93][94].…”
Section: Discussionmentioning
confidence: 80%
“…All in all, our study opens the way for the investigation of microgels at the interface as a simple realization of 2D elastic particles. We expect that the evidence reported here will have important consequences on the study of twodimensional elastic objects at the fundamental level [90,91] and for the clever design of composite materials [92][93][94].…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, the topdown approach may offer some level of control over the microgel particle properties by fine-tuning the macrogel structure, since at least some characteristics of the microgel are expected to be inherited from the initial macrogel, e.g. the internal cross-link density in the microgel (Murray 2019a). Thus specific ''gel recipes'' can be designed in order to produce macrogels with a certain desired microscopic structure: for example, more brittle, highly porous heterogenous gels break down more easily to give microgels with a narrower and smaller size distribution compared to gels which are elastic and homogenous (Saavedra Isusi et al 2019).…”
Section: Complex Formationmentioning
confidence: 99%
“…compressive, tensile or shear) and its magnitude applied during top-down processing also affects how a gel breaks down (Saavedra Isusi et al 2019). Processing may deform and alter the gel network structure, often leading to a more open structure in the microgel particles (Murray 2019a). It has been reported that pectin-based microgels are more easily broken down when conditions favouring extensional forces were employed, for example laminar flow in a rotorstator device, since the tensile strength of the gels was lower than the compressive strength (Saavedra Isusi et al 2019).…”
Section: Complex Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 This however rises the question if due to the solvent penetrability the definition of any contact angle has any sense in such systems. 11,14 Anyhow, it is evident that alternative approaches are required to understand particle conformations at interfaces.…”
Section: Introductionmentioning
confidence: 99%